Pressure Coefficients Acting Upon the Cylinder Obtained by Numerical and Experimental Analysis - Medvecká Soňa; Ivánková Oľga; Macák Marek (Civil and Environmental Engineering, 2017)
Analysis of wind flow acting upon high-rise buildings is a very common topic. This paper deals with experiment in the Boundary Layer Wind Tunnel (BWLT) in Bratislava and comparison with the computational fluid dynamics (CFD) simulation and values given in the Eurocode. The analyzed object was the model of building with circular cross section (cylinder). External wind pressure coefficients were compared in three height levels of model.